Subjective cognition in adults with common psychiatric classifications; a systematic review. (February 2022) - Groenman, Annabeth P.; van der Werf, Sieberen; Geurts, Hilde M.
Highlights: Subjective cognitive complaints (SCCs) are found in all psychiatric classifications. SCCs show inconsistent and low associations to objective cognition across classifications. SCCs reflect suffering andbehavioral problems experienced by those with psychiatric problems. Abstract: The aim is to assess whether instruments developed to measure subjective cognitive complaints (SCCs) and in neurology and aging can reliably be used in ADHD and other common psychiatric classifications. MEDLINE, PsycINFO, CINAHL and EMBASE+EMBASE CLASSIC were searched for relevant work on SCCs in psychiatric classifications (ADHD, autism, mood disorders, schizophrenia) in two phases: 1 identify instruments, 2 relevant studies. 35 studies with varying study quality were included. SCCs are most commonly studied in ADHD and mood disorders, but are found in all psychiatric classifications. SCCs show inconsistent and low associations to objective cognition across disorders, but higher and consistent relations are found with behavioral outcomes. SCCs are not qualitatively different for ADHD compared to other psychiatric classifications, and should thus not be seen as analogous to well validated measures of objective cognition. However, SCCs do reflect suffering, behavioral difficulties and problems experienced by across those with psychiatric problems in daily life.